The role of amikacin in the treatment of nontuberculous mycobacterial disease. (13th October 2021) - Raaijmakers, Jelmer; Schildkraut, Jodie Anne; Hoefsloot, Wouter; van Ingen, Jakko
ABSTRACT: Introduction : Guidelines recommend the use of amikacin in the treatment of nontuberculous mycobacterial (NTM) disease. The authors have evaluated the evidence for the position of amikacin in NTM disease treatment. Areas covered : The authors performed a literature search for original research on amikacin in NTM disease, including its mechanism of action, emergence of resistance, pre-clinical and clinical investigations. Expert opinion : Amikacin shows moderate in vitro activity against the clinically most relevant NTM species ( M. avium complex and M. abscessus ). It is synergistic with ethambutol, clofazimine, and macrolides and these combinations are effective in animal models. Liposomal encapsulation increases amikacin efficacy. Clinically, the recommended dose of 15 mg/kg intravenous amikacin does not lead to PK/PD target attainment in all patients and a positive impact on long-term treatment outcomes remains unproven in both M. avium complex and M. abscessus disease. Adding the amikacin liposome inhalation suspension did prove to be effective in short and long term in patients not responding to recommended treatment for M. avium complex pulmonary disease. Its optimal use in M. avium complex and M. abscessus pulmonary disease warrants further evaluation.